Use of Non-pharmacological Therapies in Individuals With Migraine Eligible for Treatment With Monoclonal Antibodies Targeting Calcitonin Gene-Related Peptide (CGRP)-Signaling: A Single-Center Cross-Sectional Observational Study - Rundblad, Lucas; Cullum, Christopher Kjaer; Sacco, Simona; Gil-Gouveia, Raquel; Uludüz, Derya; Do, Thien Phu; Amin, Faisal Mohammad (Frontiers in Pain Research, 2022)
Introduction: Accessibility oftreatment with monoclonal antibodies targeting the calcitonin gene-related peptide (CGRP) signaling pathway is impeded by regulatory restrictions. Affected individuals may seek out other services including non-pharmacological therapies. Thus, we found it timely to ascertain the use of non-pharmacological therapies in individuals with treatment-resistant migraine eligible for and naïve to treatment with CGRP-signaling targeting monoclonal antibodies. Methods: We conducted a single-center cross-sectional observational study of patients eligible and naïve to treatment with monoclonal antibodies targeting CGRP or its receptor. We recorded demographical information (gender, age, educational level, employment status, income), disease burden (frequency of headache days and migraine days), previous use of preventive pharmacological medications for migraine, and use of non-pharmacological therapies the past 3 months including frequency of interventions, costs, and patient-reported assessment of efficacy on a 6-point scale. Results: We included 122 patients between June 17, 2019, and January 6, 2020; 101 (83%) were women and the mean age was 45.2±13.3 years. One-third (n=41 [34%]) had used non-pharmacological therapy within the past 3 months. Among these participants, median frequency of different interventions was 1 (IQR: 1-2), median number of monthly visits was 2.3 (IQR: 1.3-4), mean and median monthly costs were 1086±1471 and 600 (IQR: 0-1200) DKK (1 EUR = 7.5 DKK), respectively, and median assessment of efficacy of interventions was 2 (IQR: 0-3). Conclusions: Even in a high-income country with freely accessible headache services, there was a non-negligible direct cost in parallel with a low satisfaction for non-pharmacological therapies amongst patients at a tertiary headache center.